T The Influence of People's Business Credit (KUR) on the Income of MSME Customers at PT Bank Negara Indonesia KCP Rappang. - Hasriyanti, Hasriyanti; Kumala Putri, Andi Sri; Lisra, Lisra (Paser Institute Of Accounting and Finance, 2025)
People's Business Credit (KUR) is providing or lending money to people who want to open a business that is constrained by capital or to people who want to develop their business, especially MSMEs. So this study was conducted to find out whether KUR has a significant effect on MSME income. The type of research is quantitative descriptive, which distributes questionnaires to MSME actors who take KUR funds with a sample of 42 people. The results of this study show that People's Business Credit (KUR) has a positive and significant effect on MSME income at PT Bank Negara Indonesia Kcp Rappang. This was seen after carrying out several SPSS testing methods such as testing validity, reliability, classical assumption tests, partial tests or t tests and R determinant tests.